Acute traumatic coagulopathy: The elephant in a room of blind scientists. Issue 6 (June 2017) - Meledeo, Michael A.; Herzig, Maryanne C.; Bynum, James A.; Wu, Xiaowu; Ramasubramanian, Anand K.; Darlington, Daniel N.; Reddoch, Kristin M.; Cap, Andrew P.
Abstract : ABSTRACT: Acute traumatic coagulopathy (ATC) is the failure of coagulation homeostasis that can rapidly arise following traumatic injury, hemorrhage, and shock; it is associated with higher injury severity, coagulation abnormalities, and increased blood transfusions. Acute traumatic coagulopathy has historically been defined by a prolonged prothrombin time, although newer, more informative measurements of hemostatic function have been used to improve diagnosis and support clinical decision making. The underlying biochemical mechanisms of and best practice therapeutics for ATC remain under active investigation because of its significant correlation to poor outcomes. The wide range of hypothesized mechanisms for ATC results from the large number of symptoms, phenotypes, and altered states in these patients as observed by multiple research groups. Much like the ancient fable of blind men describing an elephant from their limited perspectives, the limited nature of clinical and laboratory tools used to diagnose coagulopathy or evaluate hemostatic function has made finding causation difficult. The prolonged prothrombin time, degree of fibrinolysis, depletion of coagulation factors and inhibitors, and general failure of the blood have all been identified as being primary indicators for ATC. Therapeutic interventions including recombinant coagulation factors, antifibrinolytics, and blood products have been used with varying degrees of success as they are used to address specific symptoms. To truly understand the causes of ATC, research efforts must recognize the complexity of the hemostatic system and get to the heart of the matter by answering the question: "Is ATC a pathological condition that develops from the observed deficiencies in coagulation, fibrinolysis, and autoregulation, or is ATC an adaptive response generated as the body attempts to restore perfusion and avoid massive organ failure?" Because patient management must proceed without definitive answers regarding the entire causative chain, the current therapeutic focus should be on using what knowledge has been gained to the patient's advantage: control hemorrhage, maintain appropriate homeostatic balances of coagulation proteins, and restore oxygen perfusion.